Resistance to Sexual Harassment by Cassandra in Promising Young Woman (2020) - Oktatiara, Hari Tata (Universitas Negeri Surabaya, 2024)
This research explores the resistance to sexual harassment based on the theory proposed by Steve Pile and Michael Keith carried out by Cassandra or Cassie as the main character in Emerald Fennell's Promising Young Woman (2020) and also the impact that occurred in her personal life after she became a victim of sexual harassment by men. This analysis shows how the main character's efforts to fight sexual harassment against the perpetrator who harassed her and her friend in the past so that she had to end her life, as well as depicting a strong female figure for herself in achieving justice for fellow female victims of sexual harassment which is very much in line with third wave feminism which fights for justice for female victims of sexual harassment.